Computational study of amiloride – a WADA banned molecule - Svetlana Pelemiš; Sanja J. Armaković; Bogdan T. Tomić; Stevan Armaković (Journal of Engineering & Processing Management, 2021)
Amiloride (AMI) is a representative of diuretics. Among other purposes, it is utilized for high blood pressure or swelling induced by heart failure. While it is identified as one of the safest medicines available, it is also listed in the World Anti-doping Agency’s list of substances banned in sport, because it is considered a masking agent. Since it has been abused in sports, methods have been developed to be able to detect it during doping controls. We have computationally investigated selected structural and reactive properties of the AMI molecule in this work, employing density functional theory calculations.
Keywords: Amiloride; DFT; reactivity; structure